2021
DOI: 10.1002/celc.202100183
|View full text |Cite
|
Sign up to set email alerts
|

A Low‐Cost Al‐Graphite Battery with Urea and Acetamide‐Based Electrolytes

Abstract: Al‐ion batteries employing natural graphite cathodes have been proposed as a valid alternative to Li‐ion systems due to their low‐cost and sustainability, as well as a stable long‐term cycle life. In contrast to commonly used but typically expensive ionic‐liquid‐based electrolytes, our reported Al‐graphite batteries use AlCl3/urea and AlCl3/acetamide deep eutectic solvents (DES, also known as ionic liquid analogues) as low‐cost alternative. By carefully selecting amide composition, Al speciation in the DES ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Currently, DES is mainly used as a novel electrolyte in the field of LIBs. Jach Franziska et al [ 30 ] used AlCl 3 /urea and AlCl 3 /acetamide DES as electrolytes in Al–graphite battery; the practical applicability was demonstrated using long‐term cycling experiments with >8000 cycles, exhibiting a specific capacity of around 50 mAh g −1 at a current rate of 2 A g −1 . Hu et al [ 31 ] reported a dual‐anion DES based on elaborately selected combination of nitrite and functional lithium salts.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, DES is mainly used as a novel electrolyte in the field of LIBs. Jach Franziska et al [ 30 ] used AlCl 3 /urea and AlCl 3 /acetamide DES as electrolytes in Al–graphite battery; the practical applicability was demonstrated using long‐term cycling experiments with >8000 cycles, exhibiting a specific capacity of around 50 mAh g −1 at a current rate of 2 A g −1 . Hu et al [ 31 ] reported a dual‐anion DES based on elaborately selected combination of nitrite and functional lithium salts.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to lead to slow reduction kinetics. A large number of recent studies have focused on urea-based ILA electrolytes as an alternative to 1-ethyl-3-methylimidazolium chloride (EMIM-Cl) in order to provide a more cost-effective solution for ABB systems. Recently, this topic was reviewed .…”
Section: Introductionmentioning
confidence: 99%
“…[14] To mitigate the cost issue, AlCl 3 based ILs made with cheaper Lewis basic ligands should be developed. Recently, works with urea (80 mAh g À 1 @100 mA g À 1 ), [15,16] triethylamine hydrochloride (TEA) (88 mAh g À 1 @100 mA g À 1 ), [17] trimethylamine hydrochloride (TMA) (83 mAh g À 1 @100 mA g À 1 ) [18] and acetamide [16] (67 mAh g À 1 @100 mA g À 1 ) with comparable specific cell capacity were published. Especially, TEA-AlCl 3 is of great economical interest since industrial grade TEA is thousand times cheaper than EMIMCl.…”
Section: Introductionmentioning
confidence: 99%